Migrant inflows, capital outflows, growth and distribution: should we control capital rather than immigration? - Emiliano Brancaccio; Andrea Califano; Fabiana De Cristofaro (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
Liberalization policies of international movements of capital and labour have represented a crucial feature of the so-called 'globalization' era. More recently, however, several restrictions on migratory movements have been adopted to face the alleged negative effects of immigration. On the contrary, free movement of capital has almost always been preserved. This paper aims to verify whether this current framework of international economic policy can be justified in economic terms. We propose an unprecedented direct comparison between the macroeconomic and distributive impacts of 'extreme' episodes of net capital outflows and net migrant inflows in OECD countries between 1970 and 2017. Applying a fixed-effects approach and an event-study approach, we show that GDP growth and functional income distribution have null or even positive statistical relationships with immigration, while they have largely negative statistical relationships with capital flights. More specifically, extreme migrant inflows are not related or in some cases are positively related to real GDP growth, real GDP per capita growth and the wage share, while extreme capital outflows are negatively related to real GDP growth and real GDP per capita growth. These results contrast with current policy agendas and seem to suggest that controls should concern capital movements rather than migratory flows of people.
Keywords: F21; F22; F32; F62; F68; 330; migrant inflows; capital outflows; GDP growth; GDP per capita; wage share; controlsof capital movement or immigration